2020
DOI: 10.4209/aaqr.2019.09.0442
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Response Measures to Alleviate a Severe Haze Pollution Event in Northern China during December 2015: Assessment of Effectiveness

Abstract: Using the WRF-Chem model, we simulated the surface PM 2.5 concentrations on the North China Plain (NCP) during a severe winter haze episode (December 6-10, 2015) with the goal of assessing the effectiveness of the implemented emergency response measures (ERMs) in alleviating the pollution. We estimated that the ERMs decreased the anthropogenic pollutant emissions, with the exception of NH 3 , by 8-48% during this event. Inputting these reduced emission estimates, our simulations reproduced the observed PM 2.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…1 A and E) at the beginning of the lockdown period although NO x showed a significant reduction in the COVID-19 episode. This is consistent with previous results that emergency measures for severe haze prevention can only weakly reduce PM 2.5 concentration ( Ma et al, 2020 ; Wang et al, 2020a ). Previous works also suggested that the chemical transformation of gaseous pollutants to secondary inorganic aerosols may lead to the explosive growth of PM 2.5 ( Chen et al, 2020a ; Sun et al, 2019b ; Wang et al, 2013 ; Zheng et al, 2015 ; Zhong et al, 2018 ).…”
Section: Resultssupporting
confidence: 93%
“…1 A and E) at the beginning of the lockdown period although NO x showed a significant reduction in the COVID-19 episode. This is consistent with previous results that emergency measures for severe haze prevention can only weakly reduce PM 2.5 concentration ( Ma et al, 2020 ; Wang et al, 2020a ). Previous works also suggested that the chemical transformation of gaseous pollutants to secondary inorganic aerosols may lead to the explosive growth of PM 2.5 ( Chen et al, 2020a ; Sun et al, 2019b ; Wang et al, 2013 ; Zheng et al, 2015 ; Zhong et al, 2018 ).…”
Section: Resultssupporting
confidence: 93%
“…Alternatively, GEOS-Chem can also use a volatility basis set (VBS) scheme (Robinson et al, 2007;Pye et al, 2010) to calculate complex SOA formation from the oxidation of monoterpenes, sesquiterpenes, and light aromatics. The complex SOA scheme also includes SOA formed via the aqueous-phase reactions of oxidation products from isoprene (Marais et al, 2016). GEOS-Chem assumes static, lognormal dry size distributions for its simulated bulk aerosol species (except dust), as well as prescribed aerosol hygroscopicity and optical properties at multiple wavelengths under different relative humidity, for photolysis and heterogeneous chemistry calculations (Köpke et al, 1997;Martin et al, 2003;Drury et al, 2010;Jaeglé et al, 2011;Latimer and Martin, 2019).…”
Section: 21mentioning
confidence: 99%
“…For example the Asia-Pacific Economic Cooperation (APEC) summit in 2016, the summit for the Group of Twenty (G20) in 2016 and the 19 th National Congress of the Communist Party of China (NCCPC) in 2017. These case studies suggested that temporary control measures were effective in improving air quality (Xu et al, 2017;Ansari et al, 2019;Wang et al, 2019;Ma et al, 2020;Zhang et al, 2020). However, the internal mechanisms of pollution reduction may still be complicated.…”
Section: Introductionmentioning
confidence: 99%